2014
DOI: 10.4236/jbise.2014.713099
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Gene Knockout Reduces the Expression of mGlu Receptor 1a/b and Decreases the Glutamate-Dependent Production of Nitric Oxide

Abstract: IL-10 provides trophic and survival effects directly on neurons, promotes axonal outgrowth, and stimulates neuroregeneration. In this study, we analyzed the activities of arginase and nitric oxide synthase (NOS) in synaptoneurosomes derived from brain cortex of C57BL/6 IL-10 gene-knockout (KO) and wild-type (Wt) mice and determined that the synaptoneurosomes derived from KO mice present lower arginase II activity and lower spermine content than those derived from Wt mice, whereas the basal NOS activity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Our previous investigation has shown that the total level of the subunits of NMDAR (NR2A and NR2B), as well as the level of NMDAR-bound nNOS, are not changed in KO mice. Despite this, NMDAR from KO mice has different ligand-binding properties and exhibits significantly lower sensitivity to polyamines [ 10 ]. These data suggests that IL-10 deficient mice are comprising splicing isoforms of NMDAR, which may have higher sensitivity to the protective actions of SigR1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous investigation has shown that the total level of the subunits of NMDAR (NR2A and NR2B), as well as the level of NMDAR-bound nNOS, are not changed in KO mice. Despite this, NMDAR from KO mice has different ligand-binding properties and exhibits significantly lower sensitivity to polyamines [ 10 ]. These data suggests that IL-10 deficient mice are comprising splicing isoforms of NMDAR, which may have higher sensitivity to the protective actions of SigR1.…”
Section: Resultsmentioning
confidence: 99%
“…IL-10 can change long-term potentiation, suggesting that a target of the cytokine is the system participating in glutamatergic neurotransmission [ 9 ]. An IL-10 deficiency reduces the expression of mGlu-receptor 1a/b, decreases the sensitivity of NMDA-receptor to the polyamines and changes the glutamate-dependent production of nitric oxide [ 10 ]. In addition to an activation of the canonical signaling pathways, this cytokine is capable of exerting the rapid neuroprotective effects through inhibition of inositol-3-phosphate receptor (IP3R)-sensitive Ca 2+ release from internal stores after repeated NMDA receptor stimulation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%